The MBA labour market: A note on the global perspectives for graduates in 2015 - Heijman, Wim (Applied Studies in Agribusiness and Commerce, 2016)
What are the labour market perspectives for MBA graduates in 2015? Each year the GMAC carries out a year-end poll to find out the hiring plans of the employers with respect to graduates in business studies. This short notes presents the most important results for MBA graduates.